2013
DOI: 10.1523/jneurosci.5351-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-Mediated Stabilization of Fusion Pores in Cultured Rat Pituitary Lactotrophs

Abstract: Regulated exocytosis mediates the release of hormones and transmitters. The last step of this process is represented by the merger between the vesicle and the plasma membranes, and the formation of a fusion pore. Once formed, the initially stable and narrow fusion pore may reversibly widen (transient exocytosis) or fully open (full-fusion exocytosis). Exocytosis is typically triggered by an elevation in cytosolic calcium activity. However, other second messengers, such as cyclic AMP (cAMP), have been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 55 publications
3
30
0
Order By: Relevance
“…-triggered exocytosis of ANP has been observed in astrocytes pretreated with the membrane-permeable cAMP analogue dibutyryl cAMP [65]. Whether cAMP triggers the fusion of gliosignal vesicles de novo or only modulates the fusion pore dynamics of already pre-fused vesicles by increasing the size and open time of a fusion pore between the vesicle and the plasma membrane, as has been observed in neuroendocrine cells [66], is not known.…”
Section: Gpcr-mediated Astrocytic Excitabilitymentioning
confidence: 97%
“…-triggered exocytosis of ANP has been observed in astrocytes pretreated with the membrane-permeable cAMP analogue dibutyryl cAMP [65]. Whether cAMP triggers the fusion of gliosignal vesicles de novo or only modulates the fusion pore dynamics of already pre-fused vesicles by increasing the size and open time of a fusion pore between the vesicle and the plasma membrane, as has been observed in neuroendocrine cells [66], is not known.…”
Section: Gpcr-mediated Astrocytic Excitabilitymentioning
confidence: 97%
“…Second messengers may also amplify the Ca 2þ signal by enhancing trafficking of exocytotic vesicles to the plasma membrane (1)(2)(3). The main signal for insulin secretion from pancreatic b cells, in contrast, is glucose metabolism, which raises Ca 2þ by closure of ATP-dependent K þ (K(ATP)) channels.…”
Section: Introductionmentioning
confidence: 99%
“…HCN2 channels modulate exocytosis It was shown previously that an increase in intracellular second messenger cAMP affects exocytotic events in cultured pituitary lactotrophs 19 and that some of the modulations are mediated by HCN channels, which are expressed in the plasma membrane and in the membrane of secretory vesicles. 24 If the plasma membrane-resident HCN channels are activated, then this may increase the local [Ca 2C ] i , a stimulus known to increase the exocytotic activity.…”
Section: Resultsmentioning
confidence: 99%
“…If such a region is associated with the fusion pore, then the accumulation of ions (at the cytoplasmic or extracellular side) could affect the stability and local curvature of the pore, as proposed by Kabaso et al 18 Recently, we reported that Hyperpolarization-activated Cyclic Nucleotide-gated (HCN) channels modulate fusion pore properties. 19 HCN channels are permeable to cations (Na C , K C and Ca 2C ) [20][21][22] and likely affect exocytosis indirectly by increasing the local [Ca 2C ] i , but may also contribute directly via electrostatic interactions with charged membrane constituents near the fusion pore. Here, we assessed the contribution of electrostatic interactions, mediated by extracellular diand trivalent cations, to changes in fusion pore conductance, a parameter reporting pore geometry and in particular fusion pore diameter.…”
Section: Introductionmentioning
confidence: 99%